De la Epiméleia heautu en Sócrates a la inquietud por el sujeto en psicoanálisis (2013)
ABSTRACT: Michel Foucault's thinking moved from the relationships between the subject and the apparatus of power to a conception that seeks to vindicate the relationships between the subject and truth. Such conception is in the context of an imperative forgotten by the Modern thinking that reached its apex under the assertion “I think, therefore I am.” This imperative, from a Foucauldian perspective, is in the terms of a “care of the self”, which becomes a form of asceticism where it is necessary to return in order to restore the forgotten relationship between the subject and truth. This text is a reflection on psychoanalysis as a possible practice that restores the care of the self, taking into account its specificity, so that a theory that has the subject as an axial element must also take into account a fundamental question: what is psychoanalysis concerned about? What is the nature of this subject?